Impact of social capital, harassment of women and girls, and water and sanitation access on premature birth and low infant birth weight in India. - Kelly K Baker; William T Story; Evan Walser-Kuntz; M Bridget Zimmerman (PLoS ONE, 2018)
BACKGROUND:Globally, preterm birth (PTB) and low infant birth weight (LBW) are leading causes of maternal and child morbidity and mortality. Inadequate water and sanitation access (WASH) are risk factors for PTB and LBW in low-income countries. Physical stress from carrying water and psychosocial stress from addressing sanitation needs in the open may be mechanisms underlying these associations. If so, then living in a community with strong social capital should be able to buffer the adverse effects of WASH on birth outcomes. The objective of this study is to assess the relationships between WASH access and social conditions (including harassment and social capital) on PTB and LBW outcomes among Indian women, and to test whether social conditions modified the association between WASH and birth outcomes. METHODS AND FINDINGS:This cohort study examined the effect of pre-birth WASH and social conditions on self-reported PTB status and LBW status for 7,926 women who gave birth between 2004/2005 and 2011/2012 Waves of the India Human Development Survey. PTB and LBW occurred in 14.9% and 15.5% of women, respectively. After adjusting for maternal biological and socioeconomic conditions, PTB was associated with sharing a building/compound latrine (Odds Ratio (OR) = 1.55; 95% Confidence Interval (CI) = 1.01, 2.38) versus private latrine access, but suggested an effect in the opposite direction for sharing a community/public latrine (OR = 0.67; CI = 0.45, 1.01). Open defecation, type of drinking water source, minutes per day spent fetching water, and one-way time to a drinking water source were not associated with PTB. LBW was associated with spending more than two hours per day fetching water compared to less than two hours (OR = 1.33; CI = 1.05, 1.70) and suggested an association with open defecation (OR = 1.22; CI = 1.00, 1.48), but was not associated with other types of sanitation, type of drinking water source, or time to a drinking water source. Harassment of women and girls in the community was associated with both PTB (OR = 1.33; CI = 1.09, 1.62) and LBW (OR = 1.26; CI = 1.03, 1.54). The data also showed a possible association of local crime with LBW (OR = 1.30; CI = 1.00, 1.68). Statistically significant (p<0.05) evidence of effect modification was only found for collective efficacy on the association between type of sanitation access and PTB. In addition, stratified analyses identified differences in effect size for walking time to the primary drinking water source and PTB by crime, sanitation access and PTB by harassment, and total hours per day fetching water and LBW by collective efficacy. Limitations of this observational study include risk of bias, inability to confirm causality, reliance on self-reported outcomes, and limited sub-group sample sizes for testing effect modification. CONCLUSIONS:The relationship between adverse birth outcomes and sanitation access, domestic water fetching, crime, and gender-based harassment suggests physical and psychosocial stress are possible mechanisms by which WASH access affects PTB and LBW among Indian women. Interventions that reduce domestic responsibilities related to water and sanitation and change social norms related to gender-based harassment may reduce rates of PTB and LBW in India.